Hypervitaminosis B12 - Koprivica, Marko M; Bjelanović, Jelena (Medicinski časopis, 2022)
Increased concentrations of vitamin B12 are the result ofexcessive intake of this vitamin, increased release of vitaminsfrom hepatic depots, or elevated concentrations oftranscobalamin resulting from the increased production orreduced decomposition of this molecule. The most commondiseases that lead to B12 hypervitaminosis are malignanciesand solid tumours. As a result of elevated concentrations,acnes emerge or exacerbate the already existing acneiformchanges. Rosacea fulminant, allergic, and otheranaphylactic reactions may also develop. The aim of thestudy was to determine the effect of increased concentrationsof vitamin B12 onto human health. In a study conducted byDeneuvil and associates, the elevated B12 vitamin levelswere observed in 12% of respondents. In the study by Carmeland associates, 14% of the respondents had highcobalanemia. The results of other studies show that theprevalence of high cobalanemia is 13%, while very highcobalanemia is registered in 7% of cases. In the multicentricBDOSE study, the incidence of high serum cobalamin was18%. The increased concentrations of cobalamin are mostcommonly caused by a disease, while disorders due toinadequate intake and overdose are much less common. As aresult of B12 hypervitaminosis, acnes emerge orexacerbation of the pre-existing acneiform changes mayoccur. In addition to acne, other dermatological diseases(Rosacea fulminant, dermatitis) may develop as a result ofhypervitaminosis, followed by allergic and anaphylacticreactions.
Keywords: Vitamin B12, hypervitaminosis, acne